2018
DOI: 10.1016/j.ssmph.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

The association between women's sanitation experiences and mental health: A cross-sectional study in Rural, Odisha India

Abstract: Emerging qualitative research suggests women’s sanitation experiences may impact mental health. However, specific associations remain unclear. We aimed to determine if sanitation access and sanitation experiences were associated with mental health among women in rural Odisha, India. Using a cross-sectional design, we evaluated the association between sanitation access and sanitation experiences and selected mental health outcomes. Data were collected from 1347 randomly selected women across four life course st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 59 publications
1
59
0
Order By: Relevance
“…Third, our survey measures were developed and validated in similar peri-urban communities in Tamil Nadu, India, which could be context-specific. However, evidence from rural Odisha (India) that highlighted similar psychosocial stressors suggests these measurements and findings may be applicable in similar contexts [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, our survey measures were developed and validated in similar peri-urban communities in Tamil Nadu, India, which could be context-specific. However, evidence from rural Odisha (India) that highlighted similar psychosocial stressors suggests these measurements and findings may be applicable in similar contexts [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate menstrual hygiene management is also tied to school absenteeism for girls, which highlights the disproportionate impact on women who do not have adequate access to sanitation [39]. These negative experiences, both external, such as shaming or gossip, as well as internal, such as guilt or shame, may have long-term impacts on mental health and well-being [40]. Therefore, understanding gender differences in the social beliefs related to sanitation behaviors and how these social beliefs relate to each other can inform gendered sanitation interventions.…”
Section: Plos Onementioning
confidence: 99%
“…Moreover, because the burden of water fetching is typically borne by women and girls (Crow & McPike, 2009;Geere & Cortobius, 2017;Graham, Hirai, & Kim, 2016), these activities can be physically dangerous given the risk of falls or sexual assault (Bisung & Elliott, 2017a, 2017bCollins et al, 2017, Pommells, Schuster-Wallace, Watt, & Mulawa, 2018. For example, in a study of women in Pune, India, Hirve et al (2015) pointed to women's fears of attacks from people, animals, or insects when openly defecating (see also Caruso et al, 2017Caruso et al, , 2018Corburn & Hildebrand, 2015;O'Reilly, 2016;Sahoo et al, 2015;Sommer et al, 2015;Winter & Barchi, 2016). In another study in Zimbabwe, women reported worries around sexual assault while queuing at boreholes (Mukuhlani & Nyamupingidza, 2014).…”
Section: Candidate Mechanism 3: Worry About Threats To Healthmentioning
confidence: 99%
“…This information indicated lack of freedom for decision making processes among the tenant group [11].…”
Section: Resultsmentioning
confidence: 99%